Task allocation and scheduling system - Ting, Zhi Ying (Nanyang Technological University, 2023)
The Multi-School Online Timetable System (MSOTPS) is a web application designed to improve the efficiency and sustainability of course and timetable scheduling for various schools at Nanyang Technological University (NTU). The project builds on the existing Timetable Planning and Scheduling System (TPS) while addressing its security and functionality issues. The system utilizes NodeJS, ReactJS, and MySQL for backend, frontend, and database management, respectively. The project aims to create a secure and functional system for course coordinators and professors, which will reduce paper waste and enhance the overall learning environment. The scope of the project includes the investigation and research of suitable technologies, the understanding and implementation of UI modules, and the implementation of the required database design. The stakeholders for this project include the NTU School of Computer Science and Engineering (SCSE), the course coordinators, and the professors. The project will benefit the stakeholders by providing a more efficient, user-friendly, and sustainable online timetable system. The report discusses the external interface requirements, including the software interfaces and communication interfaces used in the project. The report concludes that the MSOTPS system will improve the scheduling process for various schools at NTU, providing a secure and efficient online platform for course coordinators and professors.